Performance-based seismic design of concrete structures and infrastructures - Plevris, Vagelis, 1976-; Kremmyda, Georgia, 1979-; Fahjan, Yasin, 1967- (Advances in civil and industrial engineering (ACIE) book series., 2017)
"This book provides contributions on Earthquake Engineering and on Performance-Based design of concrete structures. This book includes topics such as advanced methods for the seismic assessment and vulnerability of structures, strength-based and deformation-based design, and Numerical Models for the Seismic Assessment of Concrete Structures"--